Article Comparative Study of ZnO Thin Films Doped with Transition Metals (Cu and Co) for Methylene Blue Photodegradation under Visible Irradiation (2020)
We synthesized and characterized both Co-doped ZnO (ZnO:Co) and Cu-doped ZnO (ZnO:Cu) thin films. The catalysts’ synthesis was carried out by the sol–gel method while the doctor blade technique was used for thin film deposition. The physicochemical characterization of the catalysts was carried out by Raman spectroscopy, scanning electron microscopy (SEM), X-ray di raction, and di use reflectance measurements. The photocatalytic activity was studied under visible irradiation in aqueous solution, and kinetic parameters were determined by pseudo-first-order fitting. The Raman spectra results evinced the doping process and suggested the formation of heterojunctions for both dopants. The structural di raction patterns indicated that the catalysts were polycrystalline and demonstrated the presence of a ZnO wurtzite crystalline phase. The SEM analysis showed that the morphological properties changed significantly, the micro-aggregates disappeared, and agglomeration was reduced after modification of ZnO. The ZnO optical bandgap (3.22 eV) reduced after the doping process, these being ZnO:Co (2.39 eV) and ZnO:Co (3.01 eV). Finally, the kinetic results of methylene blue photodegradation reached 62.6% for ZnO:Co thin films and 42.5% for ZnO:Cu thin films.